RETHINKING THE CANON: CONTRIBUTION OF CLASSICAL CIVILIZATION TO THE FORMATION OF WESTERN POLITICAL IDENTITY - Seidi, Dembael; Firmansyah, Muhammad Andi (Universitas Padjadjaran, 2026)
This study seeks to deconstruct the linear “Great Books” narrative in the history of Western political thought using Reinhart Koselleck’s lens of Begriffsgeschichte (conceptual history). Through a biography-of-ideas analysis, it traces the transformation of key concepts such as justice, citizenship, and sovereignty across three layers of civilization: Greco-Roman, Islamic, and Judeo-Christian. The findings suggest that modern Western politics is not a direct, static inheritance from antiquity but the result of “conceptual alchemy”—a process of meaning sedimentation where Greek rationalism was filtered through Islamic administrative and philosophical lenses, synthesized by scholastic theology, and finally secularized during the Sattelzeit period. Hence, we argue that contemporary political crises are manifestations of temporal and linguistic mismatches between inherited classical concepts and a modern state machinery that has lost its historical consciousness. Consequently, the “West” must be understood not as a monolithic entity but as a discursive palimpsest shaped by cross-cultural collisions and translations.